Pengaruh Bahan Organik, Pupuk Dan Teknik Tanam Terhadap Pertumbuhan Tanaman - Berkat Jaya Gulo; Bernardus Zebua; Erwin Saputra Gea; Irvan Haviz Gea; Irifan Setia Zebua (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This research aims to evaluate the effect of organic materials, fertilizers and planting techniques on plant growth and yield. Organic materials such as compost and manure are used to increase soil fertility, while inorganic fertilizers are applied to meet the macro and micro nutritional needs of plants. The planting techniques applied include legowo planting patterns, intercropping and monoculture with various variations in plant spacing. The results showed that the combination of organic matter and inorganic fertilizer significantly increased the soil nitrogen, phosphorus and potassium content, as well as the activity of soil microorganisms. The legowo planting technique provides better sunlight absorption efficiency, thereby increasing plant photosynthesis. Overall, the combination of organic materials, fertilizer and appropriate planting techniques resulted in more optimal vegetative and generative growth compared to the control. These results show the importance of integrating nutritional management and planting techniques to increase plant productivity in a sustainable manner.